2011
DOI: 10.1080/07391102.2011.10531243
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome Positioning Pattern Derived from Oligonucleotide Compositions of Genomic Sequences

Abstract: Availability of nucleosome positioning pattern(s) is crucial for chromatin studies. The matrix form of the pattern has been recently derived (I. Gabdank, D. Barash, E. N. Trifonov. J Biomol Struct Dyn 26, 403-412 (2009), and E. N. Trifonov. J Biomol Struct Dyn 27, 741-746 (2010)). In its simplified linear form it is described by the motif CGRAAATTTYCG. Oligonucleotide components of the motif (say, triplets GRA, RAA, AAA, etc.) would be expected to appear in eukaryotic sequences more frequently. In this work w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 35 publications
4
41
1
Order By: Relevance
“…These patterns have CC and GG separated on the sequence and structure level consistent with the patterns of the RR/YY class. Rapoport et al (2011) provided a comprehensive study of the periodical distributions of sequence elements, thought to be related to nucleosome positioning in 13 different species. Their positioning regarding the nucleosome surface is consistent with the RR/YY and WW/SS classes described here or combinations thereof (Trifonov 2010).…”
Section: Ww/ss and Rr/yy Classes Of Nps Patternsmentioning
confidence: 99%
“…These patterns have CC and GG separated on the sequence and structure level consistent with the patterns of the RR/YY class. Rapoport et al (2011) provided a comprehensive study of the periodical distributions of sequence elements, thought to be related to nucleosome positioning in 13 different species. Their positioning regarding the nucleosome surface is consistent with the RR/YY and WW/SS classes described here or combinations thereof (Trifonov 2010).…”
Section: Ww/ss and Rr/yy Classes Of Nps Patternsmentioning
confidence: 99%
“…In Fig. 1 The extension patterns can also be generated by using dinucleotides or tetranucleotides, with, essentially, the same results (Rapoport et al, 2011).…”
Section: N-gram Extension Algorithmmentioning
confidence: 86%
“…The analysis boils down to rather unexpected conclusions: The major linguistically dominant code in prokaryotes is the code for amphipathic alphahelices of proteins. Surprisingly, it is very similar to the nucleosome positioning code of eukaryotes which, in its turn, is the major code of eukaryotic genomes (Rapoport et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…As an illustration, ten most frequent trinucleotides in 16mer alpha satellite HORs in human chromosome 7 are shown in Table 2, in comparison to previously computed ten most frequent trinucleotides in the genome of C. elegans 34 as comparison between evolutionary distant genomes. Out of ten most frequent trinucleotides in 16mer HOR in human chromosome 7, six are present in the genome of C. elegans too.…”
Section: Resultsmentioning
confidence: 99%
“…34,35 It was shown that Shannon's fusing can generate motifs like TTTTCGAAAA and TTTTTGAAAA 34,35 with a periodic structure on both sides of central motif, representing a nucleosome positioning patterns. Although a string similar to central motif starting with Shannon construction of trinucleotide frequencies alpha satellite HORs is found here, they do not exhibit any periodic structure to sides of the central motif (Supplementary figure 2).…”
Section: Resultsmentioning
confidence: 99%